Acid-base composite modified fly ash, and preparation method and application method thereof

CN122894948APending Publication Date: 2026-10-13GUODIAN NANJING ELECTRIC POWER TEST RES CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611338796.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

传统的化学药剂处理方法存在投加量大、易腐蚀设备、残留物易造成水体二次污染等问题

Benefits of technology

[0014]根据本发明第二方面实施例的酸碱复合改性粉煤灰,由本发明第一方面实施例的酸碱复合改性粉煤灰的制备方法制成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894948A_ABST
    Figure CN122894948A_ABST
Patent Text Reader

Abstract

The application discloses acid-alkali composite modified fly ash and a preparation method and application method thereof, and relates to the technical field of fly ash modification. The preparation method of the acid-alkali composite modified fly ash comprises the following steps: pretreatment; calcination treatment; acid modification treatment: the calcination treatment fly ash is added into a sulfuric acid aqueous solution and mixed, stirred and reacted at 60-80 DEG C, then washed, filtered and dried to constant weight; alkali modification treatment: the acid modified fly ash is mixed with a NaOH solution, stirred and reacted at 60-90 DEG C, then hydrothermally crystallized at the same temperature, vacuum filtered after the reaction, repeatedly washed with deionized water until the pH of the filtrate is within the range of 7-9, and dried at 100 DEG C for 24 hours; re-calcination treatment: the sample is subjected to second temperature-programmed calcination, and finally the acid-alkali composite modified fly ash is obtained. According to the preparation method of the acid-alkali composite modified fly ash provided in the embodiment of the application, the acid-alkali composite modified fly ash obtained has relatively strong adsorption capacity, and has relatively good effect on sewage treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater treatment and environmental protection technology, and in particular to an acid-base composite modified fly ash and its preparation and application methods. Background Technology

[0002] In the circulating cooling water treatment process of thermal power plants, system operation is mainly maintained through sewage control and water quality stabilization technologies to achieve corrosion prevention, scale inhibition, and antibacterial effects. Achieving low reagent consumption, low operating energy consumption, and avoiding secondary pollution are key challenges in circulating water treatment processes. Traditional chemical treatment methods suffer from problems such as large dosages, easy equipment corrosion, and residues that can cause secondary water pollution.

[0003] Fly ash is a major solid waste from coal-fired power plants, with a huge annual output. Formed through high-temperature calcination, it possesses a porous structure, a large specific surface area, and good chemical stability and mechanical strength, making it less prone to corroding equipment and water pollution. However, the dense surface and closed internal pore structure of fly ash limit its active sites, resulting in relatively low adsorption capacity and making it difficult to directly apply to wastewater treatment. Therefore, improvements are needed. Summary of the Invention

[0004] The present invention aims to at least solve one of the technical problems existing in the prior art. Therefore, one object of the present invention is to provide a method for preparing acid-base composite modified fly ash, wherein the acid-base composite modified fly ash obtained by the preparation method has strong adsorption capacity and good effect on wastewater treatment.

[0005] The present invention also proposes an acid-base composite modified fly ash prepared by the above preparation method.

[0006] The present invention also proposes an application method for the above-mentioned acid-base composite modified fly ash.

[0007] The method for preparing acid-base composite modified fly ash according to a first aspect of the present invention includes: Step (1), Pretreatment: Take fly ash and pass it through a 200-mesh sieve. Dry the sieved fly ash in an oven at 105°C to obtain pretreated fly ash. Step (2), calcination treatment: The pretreated fly ash obtained in step (1) is subjected to a first programmed temperature-controlled calcination to obtain calcined fly ash; Step (3), acid modification treatment: The calcined fly ash obtained in step (2) is added to sulfuric acid aqueous solution and mixed. The mixture is stirred and reacted at 60-80℃, then washed with deionized water until neutral, filtered, and dried at 100℃ to constant weight to obtain acid modified fly ash. Step (4), Alkali modification treatment: The acid-modified fly ash obtained in step (3) is mixed with NaOH solution and stirred at 60-90℃. Then, it is hydrothermally crystallized at the same temperature. After the reaction is completed, it is vacuum filtered and repeatedly washed with deionized water until the pH of the filtrate is within the range of 7-9. Then, it is dried at 100℃ for 24 hours to obtain acid-alkali modified fly ash intermediate. Step (5) Recalcination treatment: After obtaining the acid-base modified fly ash intermediate in step (4), the sample is subjected to a second programmed temperature-controlled calcination to finally obtain acid-base composite modified fly ash.

[0008] According to the method for preparing acid-base modified fly ash according to embodiments of the present invention, calcined fly ash is added to a sulfuric acid aqueous solution for treatment, which can fully dissolve the metal oxides in the fly ash and open up the pores, while avoiding excessive acid etching that damages the fly ash skeleton structure. The acid-treated fly ash is then subjected to alkali modification treatment, which can more fully reconstruct silicon and aluminum based on the pores opened by acid modification treatment, forming a richer porous structure and active sites. The alkali modification treatment further promotes the dissolution, migration and reassembly of silicon and aluminum components, and forms a new porous structure and silicon and aluminum phase with certain crystal characteristics through hydrothermal crystallization, thereby making the modified fly ash have a strong adsorption capacity and a better effect on sewage treatment.

[0009] According to some embodiments of the present invention, in step (1), the drying time is 2 hours.

[0010] According to some embodiments of the present invention, in step (2), the first programmed temperature-controlled calcination includes: starting from room temperature, heating the pretreated fly ash to 700-800°C at a heating rate of 3-5°C / min, holding it at that temperature for 3-5 hours, and then cooling it to room temperature at a cooling rate of 3-5°C / min.

[0011] According to some embodiments of the present invention, in step (3), the ratio of the calcined fly ash to the NaOH solution is 1:(3-5) g / mL; and / or, the concentration of the NaOH solution is 1-6 mol / L; and / or, in step (3), the stirring reaction time is 3-12 hours; and / or, in step (3), the hydrothermal crystallization time is 3-12 hours.

[0012] According to some embodiments of the present invention, in step (5), the second programmed temperature-controlled calcination includes: starting the sample from room temperature, heating it to 120°C at a heating rate of 5°C / min, holding it at that temperature for 1 hour, then heating it to 300°C at a heating rate of 5°C / min, holding it at that temperature for 1 hour, then heating it to 550°C at a heating rate of 3°C / min, holding it at that temperature for 2 hours, and finally naturally cooling it to room temperature to obtain acid-base composite modified fly ash.

[0013] According to some embodiments of the present invention, in the acid modification treatment, the solid-liquid mass-volume ratio of fly ash and sulfuric acid aqueous solution is 1:(5-15) g / mL; and / or, in the acid modification treatment, the concentration of sulfuric acid aqueous solution is 0.5-1 mol / L; and / or, in the acid modification treatment, the stirring reaction time is 4-8 hours.

[0014] The acid-base composite modified fly ash according to the second aspect of the present invention is prepared by the method for preparing acid-base composite modified fly ash according to the first aspect of the present invention.

[0015] The acid-base composite modified fly ash according to an embodiment of the present invention is prepared by using the preparation method of the acid-base composite modified fly ash of the first aspect of the present invention. Calcined fly ash is added to a sulfuric acid aqueous solution for treatment, which can fully dissolve the metal oxides in the fly ash, open up the pores, and avoid excessive acid etching that damages the fly ash skeleton structure. The acid-treated fly ash is then subjected to alkali modification treatment, which, based on the pores opened by acid modification, allows for more complete silicon-aluminum reconstruction, forming a richer porous structure and active sites. Alkali modification further promotes the dissolution, migration, and reassembly of silicon-aluminum components, and through hydrothermal crystallization, forms a new porous structure and a silicon-aluminum phase with certain crystal characteristics. Therefore, the modified fly ash has a strong adsorption capacity and is effective for wastewater treatment.

[0016] According to a third aspect of the present invention, a method for applying acid-base modified fly ash, wherein the acid-base modified fly ash is used to treat circulating cooling wastewater from a thermal power plant, comprising: Step (a), Adsorption treatment: Add acid-base modified fly ash to the circulating cooling wastewater and stir at room temperature; Step (b), membrane separation treatment: The circulating cooling wastewater after adsorption treatment in step (a) is subjected to membrane separation treatment to obtain purified water and retained acid-base composite modified fly ash. The retained acid-base composite modified fly ash is added to the circulating cooling wastewater in step (a) for reuse.

[0017] According to the application method of acid-base modified fly ash according to the embodiments of the present invention, the intercepted acid-base modified fly ash is added to the circulating cooling wastewater in step (a) for reuse. It is expected that the cost per ton of water treated will be reduced by more than 10% compared with the traditional chemical agent method, achieving the green water treatment goal of "treating waste with waste" and reducing the treatment cost of power plant circulating cooling wastewater. In addition, apart from the acid-base modified fly ash, no additional chemical agents need to be added in the treatment process, avoiding the secondary pollution risk brought about by the traditional chemical agent method. The treated purified water can be reused in the circulating cooling water system, reducing the amount of fresh water taken out and the amount of wastewater discharged, which has good environmental benefits.

[0018] According to some embodiments of the present invention, in step (a), the dosage of the acid-base modified fly ash is 2-10 g / L; and / or, in step (a), the stirring time is 15-60 minutes.

[0019] According to some embodiments of the present invention, in step (b), the membrane separation employs a ceramic membrane with a pore size of 400-600 nm; and / or, in step (b), the operating pressure of the membrane separation process is 0.1-0.3 MPa.

[0020] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0021] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is a schematic flowchart of a method for preparing acid-base composite modified fly ash according to some embodiments of the present invention; Figure 2 This is a schematic flowchart of the preparation method of alkali-modified fly ash according to Comparative Example 1 of the present invention. Figure 3 This is a schematic diagram of the original fly ash appearance; Figure 4 This is a schematic diagram of the appearance of fly ash after calcination at 750°C for 2 hours according to some embodiments of the present invention. Figure 5 This is a schematic diagram of a raw fly ash image obtained using a SEM (Scanning Electron Microscope). Figure 6 This is another SEM image of the original fly ash; Figure 7 This is a SEM schematic diagram of alkali-modified fly ash according to Comparative Example 1 of the present invention. Figure 8 This is another SEM schematic diagram of alkali-modified fly ash according to Comparative Example 1 of the present invention. Figure 9 This is a SEM schematic diagram of acid-base composite modified fly ash according to Example 1 of the present invention; Figure 10 This is another SEM schematic diagram of acid-base composite modified fly ash according to Embodiment 1 of the invention; Figure 11 This is another SEM schematic diagram of acid-base composite modified fly ash according to Embodiment 1 of the invention; Figure 12This is a schematic diagram comparing the XRD (X-ray Diffraction) patterns of the acid-base modified fly ash of Example 1, the alkali modified fly ash of Comparative Example 1, and the fly ash of Comparative Example 2. Figure 13 This is a schematic diagram comparing the FTIR (Fourier Transform Infrared Spectroscopy) spectra of the acid-base modified fly ash of Example 1, the alkali modified fly ash of Comparative Example 1, and the fly ash of Comparative Example 2. Figure 14 The N2 adsorption-desorption isotherms and pore size distribution diagrams of the alkali-modified fly ash of Comparative Example 1 and the fly ash of Comparative Example 2 are shown. Figure 15 The N2 adsorption-desorption isotherms and pore size distribution diagrams of the acid-base composite modified fly ash of Example 1 and the fly ash of Comparative Example 2 are shown. Figure 16 This is a comparison chart of the adsorption and removal rates of methylene blue by the alkali-modified fly ash of Comparative Example 1, the acid-alkali composite modified fly ash of Example 1, and the fly ash of Comparative Example 2. Figure 17 This is a comparison chart of the removal rates of TOC (Total Organic Carbon) in real circulating cooling wastewater by the alkali-modified fly ash of Comparative Example 1, the acid-alkali composite modified fly ash of Example 1, and the fly ash of Comparative Example 2. Figure 18 This is a diagram showing the recycling performance of acid-base composite modified fly ash according to Example 1 of the present invention. Detailed Implementation

[0022] Embodiments of the present invention are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0023] The following is for reference. Figures 1-18 A method for preparing acid-base composite modified fly ash according to an embodiment of the present invention is described.

[0024] refer to Figure 1 The method for preparing acid-base composite modified fly ash according to the first aspect of the present invention includes: Step (1), Pretreatment: Take fly ash and pass it through a 200-mesh sieve. Dry the sieved fly ash in an oven at 105°C to obtain pretreated fly ash. For example, fly ash can be solid waste fly ash from power plants. Using solid waste fly ash from power plants as raw material is widely available and inexpensive. Step (2), calcination treatment: The pretreated fly ash obtained in step (1) is subjected to a first programmed temperature-controlled calcination to obtain calcined fly ash; Step (3), acid modification treatment: The calcined fly ash obtained in step (2) is added to sulfuric acid aqueous solution and mixed. The mixture is stirred and reacted at 60-80℃, then washed with deionized water until neutral, filtered, and dried at 100℃ to constant weight to obtain acid modified fly ash. Step (4), Alkali modification treatment: The acid-modified fly ash obtained in step (3) is mixed with NaOH solution and stirred at 60-90℃. Then, it is hydrothermally crystallized at the same temperature. After the reaction is completed, it is vacuum filtered and repeatedly washed with deionized water until the pH of the filtrate is within the range of 7-9. Then, it is dried at 100℃ for 24 hours to obtain acid-alkali modified fly ash intermediate. Step (5) Recalcination treatment: After obtaining the acid-base modified fly ash intermediate in step (4), the sample is subjected to a second programmed temperature-controlled calcination to finally obtain acid-base composite modified fly ash.

[0025] For example, the temperature of the stirring reaction can be 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, etc.; by setting the temperature of the stirring reaction to 60-90℃, it is beneficial to dissolve the aluminosilicate glass and form zeolite crystals.

[0026] The initial calcination treatment of fly ash allows for thermal activation without the introduction of NaOH, removing unburned carbon and volatile components. It also structurally adjusts some of the glassy components in the fly ash, enhancing the reactivity of the silicon and aluminum components during subsequent acid and alkali modification treatments. Subsequently, acid modification removes some metal oxides and easily soluble components from the calcined fly ash, causing dissolution of the previously dense particle surface and forming or enlarging pores. This provides a more sufficient reaction interface for the subsequent alkaline solution to penetrate the particle interior. Alkali modification further promotes the dissolution, migration, and reconstruction of the silicon and aluminum components, and facilitates the formation of new silicon and aluminum structures through hydrothermal crystallization. In this application, in addition to "opening up the channels," the more important role of acid treatment is to create a more sufficient reaction interface for subsequent alkali treatment, so that the two processes of acid etching and alkali reconstruction can work synergistically, forming a continuous process of "acid etching pre-activation - alkali dissolution - silicon-aluminum reconstruction." Moreover, although the original fly ash has been pretreated at 750℃, the composition and structure of the material obtained after acid treatment, alkali treatment and hydrothermal crystallization have changed. There are still some carbonaceous / thermally decomposable residues in the resulting acid-alkali composite modified material. Therefore, adding a recalcination treatment can not only further remove the carbonaceous and other thermally decomposable components remaining in the acid-alkali treatment and hydrothermal crystallization process, reducing the impact of residues on material properties, but also further heat-treat the structure formed after acid-alkali modification, making the structure of the modified material more stable, thereby improving its stability during use.

[0027] According to the method for preparing modified fly ash according to embodiments of the present invention, by adding calcined fly ash to a sulfuric acid aqueous solution for treatment, the metal oxides in the fly ash can be fully dissolved, the pores can be opened, and excessive acid etching can be avoided to prevent damage to the fly ash skeleton structure. The acid-treated fly ash is then subjected to alkali modification treatment, which allows for more complete silicon-aluminum reconstruction based on the pores opened by acid modification treatment, forming a richer porous structure and active sites. The alkali modification treatment further promotes the dissolution, migration and reassembly of silicon-aluminum components, and forms a new porous structure and silicon-aluminum phase with certain crystal characteristics through hydrothermal crystallization. As a result, the modified fly ash has a strong adsorption capacity and a better effect on wastewater treatment.

[0028] According to some embodiments of the present invention, in step (1), the drying time is 2 hours. By setting the drying time to 2 hours, moisture in the modified fly ash can be removed, and the preparation efficiency can be improved.

[0029] According to some embodiments of the present invention, in step (2), the programmed temperature-controlled calcination includes: starting from room temperature, heating the pretreated fly ash to 700-800°C at a heating rate of 3-5°C / min, holding it at that temperature for 3-5 hours, and then cooling it to room temperature at a cooling rate of 3-5°C / min.

[0030] For example, the heating rate can be 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min, etc.; the holding and calcining temperature can be 700℃, 720℃, 740℃, 760℃, 780℃, 800℃, etc.; the holding and calcining time can be 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.; and the cooling rate can be 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min, etc.

[0031] By performing a first programmed temperature-controlled calcination in step (2) and setting the heating and cooling rates to 3-5℃ / minute, unburned carbon can be fully removed and the surface activated. This also makes the calcination process more controllable and improves the stability of fly ash materials.

[0032] According to some embodiments of the present invention, in step (3), the ratio of calcined fly ash to NaOH solution is 1:(3-5) g / mL.

[0033] For example, the mixing ratio of calcined fly ash and NaOH solution can be 1:3g / mL, 1:4g / mL, 1:5g / mL, etc.

[0034] By mixing calcined fly ash with NaOH solution at a ratio of 1:(3-5) g / mL, the amount of NaOH can be moderate. This is beneficial for fully destroying the glassy structure of fly ash, generating crystalline products, increasing the specific surface area of ​​fly ash, and creating a rich porous structure on the surface of fly ash. It also avoids excessive corrosion of fly ash by NaOH during hydrothermal crystallization.

[0035] According to some embodiments of the present invention, the concentration of the NaOH solution is 1-6 mol / L.

[0036] By adjusting the NaOH solution concentration to 1-6 mol / L, a suitable concentration of NaOH can be achieved. This concentration is beneficial for fully disrupting the glassy structure of fly ash, generating crystalline products, thereby increasing the specific surface area of ​​fly ash, improving the removal rate of methylene blue, and giving the modified fly ash good electrostatic adsorption and ion exchange capabilities.

[0037] Preferably, the NaOH solution concentration is 4 mol / L. When the NaOH concentration is increased from 1 mol / L to 4 mol / L, the methylene blue removal rate increases from 45% to over 85%. Further increasing the concentration to 6 mol / L does not significantly improve the removal rate. Therefore, 4 mol / L is selected as the preferred concentration.

[0038] According to some embodiments of the present invention, in step (3), the stirring reaction time is 3-12 hours.

[0039] For example, the stirring reaction time is 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.

[0040] By setting the stirring reaction time to 3-12 hours, it is possible to ensure that the fly ash reacts fully while also maintaining preparation efficiency.

[0041] According to some embodiments of the present invention, in step (3), the hydrothermal crystallization time is 3-12 hours.

[0042] For example, the hydrothermal crystallization time is 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.

[0043] By allowing the hydrothermal crystallization time to be 3-12 hours, the preparation efficiency can be ensured while maintaining the hydrothermal crystallization reaction of fly ash.

[0044] refer to Figure 1 According to some embodiments of the present invention, in step (5), the second programmed temperature-controlled calcination includes: starting the sample from room temperature, heating it to 120°C at a heating rate of 5°C / min, holding it at that temperature for 1 hour, then heating it to 300°C at a heating rate of 5°C / min, holding it at that temperature for 1 hour, then heating it to 550°C at a heating rate of 3°C / min, holding it at that temperature for 2 hours, and finally cooling it naturally to room temperature to obtain acid-base composite modified fly ash.

[0045] By employing a second temperature-controlled calcination process, the calcination process becomes more controllable, and impurities can be further removed, thus improving the stability of the material.

[0046] According to some embodiments of the present invention, in the acid modification treatment, the solid-liquid mass-volume ratio of fly ash and sulfuric acid aqueous solution is 1:(5-15)g / mL.

[0047] For example, the solid-liquid mass-volume ratio of fly ash and sulfuric acid aqueous solution can be 1:5 g / mL, 1:10 g / mL, 1:15 g / mL, etc.

[0048] By making the solid-liquid mass-volume ratio of fly ash and sulfuric acid aqueous solution 1:(5-15)g / mL during acid modification treatment, the pores of fly ash can be enlarged while avoiding excessive corrosion of fly ash by sulfuric acid aqueous solution.

[0049] According to some embodiments of the present invention, in the acid modification treatment, the concentration of the sulfuric acid aqueous solution is 0.5-1 mol / L.

[0050] The concentration of sulfuric acid aqueous solution can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc.

[0051] By using a sulfuric acid aqueous solution concentration of 0.5-1 mol / L during acid modification treatment, the porosity of fly ash can be enlarged while avoiding excessive corrosion of fly ash by the sulfuric acid aqueous solution.

[0052] According to some embodiments of the present invention, in the acid modification treatment, the stirring reaction time is 4-8 hours.

[0053] For example, the stirring reaction time can be 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc.

[0054] By extending the stirring reaction time to 4-8 hours during acid modification treatment, the porosity of fly ash can be expanded while avoiding excessive corrosion of fly ash by sulfuric acid aqueous solution.

[0055] The acid-base composite modified fly ash according to the second aspect of the present invention is prepared by the method for preparing acid-base composite modified fly ash according to the first aspect of the present invention.

[0056] The acid-base composite modified fly ash according to an embodiment of the present invention is prepared by using the preparation method of the acid-base composite modified fly ash of the first aspect of the present invention. Calcined fly ash is added to a sulfuric acid aqueous solution for treatment, which can fully dissolve the metal oxides in the fly ash, open up the pores, and avoid excessive acid etching that damages the fly ash skeleton structure. The acid-treated fly ash is then subjected to alkali modification treatment, which, based on the pores opened by acid modification, allows for more complete silicon-aluminum reconstruction, forming a richer porous structure and active sites. Alkali modification further promotes the dissolution, migration, and reassembly of silicon-aluminum components, and through hydrothermal crystallization, forms a new porous structure and a silicon-aluminum phase with certain crystal characteristics. Therefore, the modified fly ash has a strong adsorption capacity and is effective for wastewater treatment.

[0057] According to a third aspect of the present invention, a method for applying acid-base modified fly ash, wherein the acid-base modified fly ash is used to treat circulating cooling wastewater from a thermal power plant, comprising: Step (a) Adsorption treatment: Add the acid-base modified fly ash to the circulating cooling wastewater and stir at room temperature; Step (b) Membrane separation treatment: Perform membrane separation treatment on the circulating cooling wastewater after adsorption treatment in step (a), filter to obtain purified water and retained acid-base modified fly ash, and reuse the retained acid-base modified fly ash added to the circulating cooling wastewater in step (a).

[0058] For example, the retained acid-base modified fly ash can be reused in step (a) by adding it to the circulating cooling wastewater 1, 2, 3, 4, 5, 6, 7, 8 times, etc.

[0059] According to the application method of acid-base modified fly ash according to the embodiments of the present invention, the intercepted acid-base modified fly ash is added to the circulating cooling wastewater in step (a) for reuse. It is expected that the cost per ton of water treated will be reduced by more than 10% compared with the traditional chemical agent method, achieving the green water treatment goal of "treating waste with waste" and reducing the treatment cost of power plant circulating cooling wastewater. In addition, apart from the acid-base modified fly ash, no additional chemical agents need to be added in the treatment process, avoiding the secondary pollution risk brought about by the traditional chemical agent method. The treated purified water can be reused in the circulating cooling water system, reducing the amount of fresh water taken out and the amount of wastewater discharged, which has good environmental benefits.

[0060] According to some embodiments of the present invention, in step (a), the dosage of acid-base modified fly ash is 2-10 g / L.

[0061] For example, the dosage of acid-base modified fly ash can be 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, etc.

[0062] By adding acid-base modified fly ash at a dosage of 2-10 g / L, the acid-base modified fly ash can fully absorb impurities in circulating cooling wastewater while also reducing the treatment cost of circulating cooling wastewater.

[0063] According to some embodiments of the present invention, in step (a), the stirring time is 15-60 minutes.

[0064] For example, the stirring time can be 15 minutes, 30 minutes, 45 minutes, 60 minutes, etc.

[0065] By setting the stirring time to 15-60 minutes, the acid-base modified fly ash can fully absorb impurities in the circulating cooling wastewater, while also improving the efficiency of wastewater treatment.

[0066] According to some embodiments of the present invention, in step (b), the membrane separation uses a ceramic membrane with a pore size of 400-600 nm.

[0067] By using ceramic membranes for membrane separation, the resulting acid-base modified fly ash can be directly reused. After being reused 5 times, the TOC removal rate can still be maintained at over 80%, reducing material consumption and processing costs, and solving the problems of adsorbent loss and secondary pollution in traditional adsorption processes.

[0068] According to some embodiments of the present invention, in step (b), the operating pressure of the membrane separation process is 0.1-0.3 MPa.

[0069] For example, the operating pressure for membrane separation treatment can be 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, etc.

[0070] By setting the operating pressure of the membrane separation process to 0.1-0.3 MPa, the membrane can achieve better separation effects on purified water and retained acid-base modified fly ash.

[0071] The following is for reference. Figures 1-18 A method for preparing acid-base composite modified fly ash according to some embodiments of the present invention is described.

[0072] Comparative Example 1, refer to Figure 2 In this comparative example, fly ash from a coal-fired power plant was first taken, passed through a 200-mesh sieve, and the undersize portion was dried at 105°C for 2 hours. The dried fly ash was then placed in a muffle furnace and heated to 750°C at a heating rate of 5°C / min, held at that temperature for 5 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain calcined fly ash.

[0073] Weigh 10g of calcined fly ash and place it in a polytetrafluoroethylene reaction vessel. Add 50mL of 4mol / L NaOH solution (solid-liquid ratio 1:5 g / mL), and stir the mixture at 90℃ for 6 hours. Then, perform hydrothermal crystallization at the same temperature for 6 hours. After the reaction is complete, filter the mixture. Wash the solid with deionized water until the pH reaches 7-9, and dry it at 100℃ for 24 hours to obtain alkali-modified fly ash, denoted as sample A.

[0074] Example 1, refer to Figure 1 In this embodiment, the pretreatment and calcination treatment are performed with reference to the method of Comparative Example 1.

[0075] Weigh 10g of calcined fly ash and add 150mL of 1mol / L H2SO4 solution (solid-liquid ratio 1:15 g / mL). Stir and react at 80℃ for 4 hours. After the reaction is complete, filter the solution, wash the solid with deionized water until neutral, and dry it at 100℃ to constant weight to obtain acid-treated fly ash.

[0076] The acid-treated fly ash was placed in a polytetrafluoroethylene reaction vessel, and 50 mL of 4 mol / L NaOH solution (solid-liquid ratio 1:5 g / mL) was added. The mixture was stirred at 90°C for 6 hours, followed by hydrothermal crystallization at the same temperature for 6 hours. After the reaction was completed, the mixture was filtered, and the solid was washed with deionized water until the pH reached 7-9. The solid was then dried at 100°C for 24 hours to obtain the alkali-treated fly ash.

[0077] The alkali-treated fly ash was placed in a muffle furnace and calcined under controlled temperature according to the following procedure: the temperature was increased from room temperature to 120°C at 5°C / min and held for 1 hour; the temperature was increased to 300°C at 5°C / min and held for 1 hour; the temperature was increased to 550°C at 3°C / min and held for 2 hours; and then naturally cooled to room temperature to obtain acid-alkali composite modified fly ash, which was designated as sample B.

[0078] Comparative Example 2, Take the raw fly ash from Comparative Example 1 after sieving and drying, and denote it as Sample C. Do not perform any modification treatment.

[0079] The characteristics of samples A, B, and C were performed, and the results are as follows: Scanning electron microscopy (SEM) analysis: such as Figure 5-11 As shown, the surface of the original fly ash (sample C) is relatively smooth, and the particles are mostly regular spherical; the surface of the alkali-modified fly ash (sample A) becomes rough, with obvious etching and pore structure; the surface of the acid-alkali composite modified fly ash (sample B) undergoes further changes, the spherical structure basically disappears, and a flower-like / plate-like hierarchical structure is formed, resulting in a richer porous structure.

[0080] X-ray diffraction (XRD) analysis: such as Figure 12 As shown, the original fly ash mainly exhibits characteristic peaks of quartz and mullite; new diffraction peaks appeared in the modified sample, indicating the formation of new crystalline phases, such as P-type zeolite. The acid-base modified sample showed more diffraction peaks and higher peak intensities than the alkali-modified sample. This indicates that the synergistic acid-base modification promoted the structural transformation of fly ash from a disordered glassy state to one with certain crystalline characteristics, improving the material's degree of order and structural stability.

[0081] Fourier Transform Infrared Spectroscopy (FTIR) Analysis: such as Figure 13 As shown, the modified sample at 1000–1100 cm⁻¹ - ¹Within the range and ~3400 cm - The enhanced hydroxyl absorption peak at ¹ indicates a change in surface functional groups, transforming the material from a highly disordered state to a relatively stable porous structure. The acid-base synergistic modification causes fly ash to undergo a dissolution and reconstruction process, thereby forming a modified material with high surface activity and good structural stability.

[0082] Specific surface area (BET) analysis: such as Figures 14-15 As shown in Table 1, the specific surface area of ​​sample C is 2.39 m² / g; the specific surface area of ​​sample A increases to 54.45 m² / g; and the specific surface area of ​​sample B further increases to 56.31 m² / g, with significant increases in pore volume and pore size.

[0083]

[0084] Table 1. Specific surface area and pore size of fly ash before and after modification A 20 mg / L methylene blue solution was prepared and added to samples A, B, and C at a concentration of 2 g / L. The mixture was stirred at room temperature for 60 minutes for adsorption. Samples were taken every 10 minutes, filtered through a 0.45 μm filter, and the absorbance was measured at 664 nm. The removal rate was calculated, and the results are shown below. Figure 8 As shown.

[0085] from Figure 16 It can be seen that the removal rate of methylene blue by sample C (raw fly ash) is only about 10%, which is due to the dense surface and underdeveloped pores of the original fly ash, resulting in a limited number of active sites. The removal rate of sample A (comparative example 1, alkali-modified) is significantly improved, reaching over 85% after 60 minutes, indicating that alkali treatment effectively opened the pores of the fly ash and increased the surface active sites. Sample B (example 1, acid-alkali modified) has the highest removal rate, approaching 100% within 10 minutes, exhibiting excellent adsorption performance. This is attributed to the acid treatment pre-opening the pores and removing impurities, allowing for more complete silica-alumina reconstruction during subsequent alkali treatment, resulting in a richer porous structure and surface hydroxyl groups.

[0086] As a cationic dye, methylene blue's adsorption process mainly relies on electrostatic adsorption and ion exchange on the surface of fly ash. Modified fly ash exhibits increased specific surface area, increased surface negative charge, and improved cation exchange capacity, thus significantly enhancing its adsorption capacity for methylene blue.

[0087] The circulating cooling wastewater (taken from the cooling tower) of a coal-fired power plant was analyzed, and its quality is shown in Table 2. This wastewater is characterized by high COD, low turbidity, high suspended solids content, and high hardness, making it a typical complex industrial wastewater system.

[0088] Samples A, B, and C were added to three equal volumes of wastewater at a dosage of 5 g / L each, and stirred at room temperature. Samples were taken at 15 and 60 minutes, filtered through a 0.45 μm filter membrane, and then the TOC was measured. The results are shown in Table 3. Figure 17 As shown, the ceramic membrane used is a 500nm ceramic membrane. The sample is first filtered through the ceramic membrane and then filtered through a 0.45 μm filter membrane.

[0089]

[0090] Table 2 Raw Water Quality of Circulating Cooling Wastewater

[0091] Table 3. Treatment effects of different fly ash samples on circulating cooling wastewater From Table 3 and Figure 17It can be seen that the acid-base modified fly ash (sample B) achieved a TOC removal rate of 83% within 15 minutes, demonstrating rapid adsorption capacity. After centrifugation for 60 minutes, the removal rate slightly decreased to 73.8%, but increased to 85.8% after ceramic membrane filtration, indicating that ceramic membrane filtration can effectively retain the desorbed organic matter and fly ash particles. The alkali-modified fly ash (sample A) showed better treatment performance than the original ash (sample C), indicating that the modification treatment significantly improved the adsorption performance of fly ash.

[0092] The suspended solids removal rate reached 100%, indicating that the ceramic membrane can completely trap fly ash particles and adsorbed suspended solids, ensuring clear effluent. In practical applications, this purified water can be directly reused in circulating cooling water systems, realizing the recycling of water resources.

[0093] The acid-base modified fly ash (sample B) prepared in Example 1 was used to treat circulating cooling wastewater under the conditions described above. After each adsorption cycle of 60 minutes, ceramic membrane separation was performed. The retained fly ash was collected and directly used for the next adsorption cycle, repeating the process five times. The TOC removal rate of the effluent after each membrane treatment was measured. The results are as follows: Figure 18 As shown, the TOC removal rate remained above 80% even after the 5th use, indicating that the material has good reusability. The removal rate decreased slightly during the recycling process, but remained at a high level overall.

[0094] Recyclability is an important indicator for evaluating the economic efficiency of adsorption materials. The acid-base composite modified fly ash prepared by this invention can be reused 5 times while still maintaining a removal rate of over 80%, which means that a unit mass of fly ash can treat 5 times the volume of wastewater, significantly reducing material consumption and treatment costs.

[0095] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0096] Although embodiments of the invention have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the claims and their equivalents.

Claims

1. A method for preparing acid-base composite modified fly ash, characterized in that, include: Step (1), Pretreatment: Take fly ash and pass it through a 200-mesh sieve. Dry the sieved fly ash in an oven at 105°C to obtain pretreated fly ash. Step (2), calcination treatment: The pretreated fly ash obtained in step (1) is subjected to a first programmed temperature-controlled calcination to obtain calcined fly ash; Step (3), acid modification treatment: The calcined fly ash obtained in step (2) is added to sulfuric acid aqueous solution and mixed. The mixture is stirred and reacted at 60-80℃, then washed with deionized water until neutral, filtered, and dried at 100℃ to constant weight to obtain acid modified fly ash. Step (4), Alkali modification treatment: The acid-modified fly ash obtained in step (3) is mixed with NaOH solution and stirred at 60-90℃. Then, it is hydrothermally crystallized at the same temperature. After the reaction is completed, it is vacuum filtered and repeatedly washed with deionized water until the pH of the filtrate is within the range of 7-9. Then, it is dried at 100℃ for 24 hours to obtain acid-alkali modified fly ash intermediate. Step (5) Recalcination treatment: After obtaining the acid-base modified fly ash intermediate in step (4), the sample is subjected to a second programmed temperature-controlled calcination to finally obtain acid-base composite modified fly ash.

2. The method for preparing acid-base modified fly ash according to claim 1, wherein in step (1), the drying time is 2 hours.

3. The method for preparing acid-base composite modified fly ash according to claim 1, wherein in step (2), the first programmed temperature-controlled calcination includes: Starting from room temperature, the pretreated fly ash is heated to 700-800℃ at a heating rate of 3-5℃ / min, and then kept at this temperature for calcination for 3-5 hours. Finally, it is cooled to room temperature at a cooling rate of 3-5℃ / min.

4. In the preparation method of acid-base composite modified fly ash according to claim 1, in step (3), the ratio of the calcined fly ash to NaOH solution is 1:(3-5) g / mL; And / or, the NaOH solution concentration is 1-6 mol / L; And / or, in step (3), the stirring reaction takes 3-12 hours; And / or, in step (3), the hydrothermal crystallization time is 3-12 hours.

5. The method for preparing acid-base composite modified fly ash according to claim 1, wherein in step (5), the second programmed temperature-controlled calcination includes: The sample was heated from room temperature to 120°C at a heating rate of 5°C / min and held for 1 hour. Then it was heated to 300°C at a heating rate of 5°C / min and held for 1 hour. Finally, it was heated to 550°C at a heating rate of 3°C / min and held for 2 hours. The sample was then allowed to cool naturally to room temperature to obtain acid-base composite modified fly ash.

6. The method for preparing acid-base modified fly ash according to claim 1, wherein in the acid modification treatment, the solid-liquid mass-volume ratio of fly ash and sulfuric acid aqueous solution is 1:(5-15)g / mL; And / or, in acid modification treatment, the concentration of sulfuric acid aqueous solution is 0.5-1 mol / L; And / or, in acid modification treatment, the stirring reaction time is 4-8 hours.

7. An acid-base composite modified fly ash, prepared by the method of any one of claims 1-6.

8. A method for applying the acid-base composite modified fly ash according to claim 7, the method being used to treat circulating cooling wastewater from a thermal power plant, comprising: Step (a), Adsorption treatment: Add acid-base modified fly ash to the circulating cooling wastewater and stir at room temperature; Step (b), membrane separation treatment: The circulating cooling wastewater after adsorption treatment in step (a) is subjected to membrane separation treatment to obtain purified water and retained acid-base composite modified fly ash. The retained acid-base composite modified fly ash is added to the circulating cooling wastewater in step (a) for reuse.

9. The application method of acid-base composite modified fly ash according to claim 8, in step (a), the dosage of acid-base composite modified fly ash is 2-10 g / L; And / or, in step (a), the stirring time is 15-60 minutes.

10. The application method of acid-base composite modified fly ash according to claim 8, in step (b), the membrane separation adopts a ceramic membrane with a pore size of 400-600 nm; And / or, in step (b), the operating pressure of the membrane separation process is 0.1-0.3 MPa.